It had to be a duke - Lorret, Vivienne (Lorret, Vivienne. Liars' club, 2023)
"Verity Hartley always tells the truth. Well, mostly. However, when her snooty neighbor returns to their small hamlet to brag about having a grand Season, a plethora of ballgowns, and so many suitors that she cannot possibly decide which one to marry, Verity tells a lie. She claims to be betrothed. To a duke. Who happens to be her family's sworn enemy. But what are the odds that he would ever learn of this one, little, harmless falsehood? Magnus Warring, the Duke of Longhurst, is on the precipice of marrying an heiress to save his estate from financial ruin. At least, he was. Until he hears an unbelievable rumor that he is already betrothed. To the daughter of a liar, cheat, and swindler! Needing to protect his reputation, he hunts down the culprit. And when he finds the untamed beguiler, she has the audacity to ask him to lie for her. To pretend to be her fiancé! One week, that's all Verity needs. Then Magnus could return to his life. But nothing is ever that simple. Sometimes it doesn't take that long to fall in love, even with the enemy"--Page 4 of cover.